Keadilan Distributif Atas Pembagian Harta Bersama yang Digunakan Sebagai Sompa Perkawinan Bugis Secara Sepihak - Lisha Trie Caesarani; Mohamad Fajri Mekka Putra (Jurnal Supremasi, 2023)
Joint assets are in the continuity of marriage until the marriage ends due to divorce, death, or because of a court decision, as well as the end of the marriage as regulated in Article 38 of the Marriage Law. Joint assets give the impact that ownership is jointly owned by husband and wife. The purpose of this study is to analyze the application of the theory of distributive justice to the division of joint property that is used as sompa unilaterally in Decision Number 276/Pdt/2020/PT Mks. Through legal research with normative juridical research methods, the following research is produced. In terms of the theory of distributive justice, the distribution of joint assets used as dowry sompa unilaterally with a portion of Â½ for men and Â½ for women do not fully contain the value of justice, because in this distribution it is necessary to consider the size of the business of the parties in the acquisition of the assets so that the parties get rights based on what they earn.